Systemic therapy & family - de Casanova, Liliana (2001)
The authors explained the Systemic Thinking beginnings, continuance and development in family therapy. This evolution was madre from the changing focus of Systemic Therapy in the interaction behacioral consequences of whe explaininig family, myths and premises whose behavior is considered problematic.